Between Managerial Competency and Moral Authority: Contextualizing Educational Leadership in Indonesian Madrasahs - Achmad A Djamil; Siti Patimah; Nurul Hidayati Murtafiah; Abdul Gani (JURNAL AL-TANZIM, 2026)
This study aims to develop a contextual leadership effectiveness framework for State Islamic Senior High Schools (MAN) in Indonesia. The study employed a qualitative multiple-case study approach across three MANs, using semi-structured interviews with madrasah principals and supported by descriptive survey data from teachers and students. The qualitative data were analyzed using thematic analysis and cross-case synthesis, while the survey data were analyzed descriptively. The results identified five leadership competency domains that, through cross-case synthesis, were integrated into four dimensions of leadership effectiveness: instructional leadership, adaptive managerial competency, relational governance, and religious moral authority. The resulting framework enriches the study of educational leadership by incorporating Islamic institutional values and provides a reference for leadership development and policy formulation in Islamic secondary education. This study provides implications for the development of Islamic educational leadership by providing a conceptual and practical framework that can serve as a basis for strengthening madrasah principal competencies, designing contextual leadership training programs, and improving Islamic educational governance that is oriented towards values, trust, and sustainable educational quality.